Intermedin Reduces Oxidative Stress and Apoptosis in Ventilator-Induced Lung Injury via JAK2/STAT3 - Fan, Shulei; He, Jing; Yang, Yanli; Wang, Daoxin (Frontiers in Pharmacology, 2022)
Mechanical ventilation is an effective treatment for acute respiratory distress syndrome (ARDS), which can improve the prognosis of ARDS to a certain extent. However, it may further aggravate lung tissue injury, which is defined as ventilator-induced lung injury (VILI). Intermedin (IMD) belongs to the calcitonin gene-related peptide (CPRP) superfamily. Our previous studies have found that IMD reduces the expression proinflammatory cytokines, down-regulates nuclear translocation and improves the integrity of endothelial barrier in ARDS. However, the effect of IMD on VILI has not been clarified. Oxidative stress imbalance and apoptosis are the main pathophysiological characteristics of VILI. In the current study, we used C57B6/J mice and human pulmonary microvascular endothelial cells (HPMECs) to establish a VILI model to analyze the effects of IMD on VILI and explore its potential mechanism. We found that IMD alleviated lung injury and inflammatory response in VILI, mainly in reducing ROS levels, upregulating SOD content, downregulating MDA content, reducing the expression of Bax and caspase-3, and increasing the expression of Bcl-2. In addition, we also found that IMD played its anti-oxidative stress and anti-apoptotic effects via JAK2/STAT3 signaling. Our study may provide some help for the prevention and treatment of VILI.